Równowaga ekologiczna w agregatowych modelach wzrostu gospodarczego jako fundamentalny czynnik realizacji strategii ekorozwoju - Dokurno, Zbigniew (The ecological equilibrium of the aggregate economic growth models as a fundamental element of sustainable development, 2006)
The main purpose of the article is to present the problem of an ecological equilibrium in the main economic-ecological balanced growth models. The other purpose of the article is to interpret an ecological equilibrium from the main methodical points of view. A value of these approaches is that they completely characterize the problem leading to the science truth. The methodological variety in seeking the solution of the ecological equilibrium leads to the conclusion that sustainable development is a very large category not only including ecological aspects.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 95-106